A Cationic Polyelectrolyte‐Controlled Liquid Mineral Precursor Process in the BaCO3 System. Issue 10 (23rd February 2015) - Zhu, Jianhua; Huang, Lei; Cui, Mingfang; Ma, Li; Cao, Fabin
Abstract: Biomimetic BaCO3 materials with various morphologies have been synthesized in a cationic polyelectrolyte‐controlled mineral solution. Investigations showed that the mineral solution initially underwent a phase separation to produce a condensed liquidlike amorphous intermediate. This mineral solution was a typical reaction‐diffusion field, in which concentric ring patterns were frequently observed. Subsequently, overgrowth fibers were seen growing on large microspheres and their growth could be interpreted in terms of a mesocrystal self‐assembly process. This work opens up the possibility of using positively charged polyelectrolytes to design a very wide range of inorganic materials. Abstract : A polymer‐induced liquid mineral precursor (PILP) provides a general pathway towards biomimetic materials with complex morphology. In this article, we expand the conception of cationic polyelectrolyte‐induced liquid precursors to other inorganic systems, such as barium carbonate. Mesocrystal fibers and a self‐organized concentric ring pattern were synthesized in the mineral solution.